Anterior Aponeurotic Approach in Congenital Ptosis - Ptozis, Konjenital; Ptozis, Aponevrotik; Cerrahisi, Levator; Ptosis, Congenital; Ptosis, Aponeurotic; Surgery, Levator (Fırat University, 2001)
The aim of this study to evaluate results of aponeurotic approached surgery in 10 eyes of 9 patients with congenital ptosis. Patient admitted to Elazig State Hospital between February 1998 and September 2000 was included in this study. Of the patients 6 six were male and 3 were female and their mean age was 15.0 (8-25) years and the mean follow up period was 11 (3-31) months. According the evaluation system used residual ptosis up to 1 mm was considered to be "successful", 1-2 mm "resonable" and residual ptosis larger than 2 mm was considered as "failure". When anterior approached levator resection was performed the rate of successful, reasonable and failure results was 70%, 20% and 10%, respectively. In conclusion, anterior approached aponeurotic surgery presents advantages including protection of Muller muscle, Whitnal ligament, conjunctiva and levator horns like anatomical structures, detailed visualisation, cosmetic and functional healing, therefore it present a prefeable method in surgical treatment of ptosis.

Bu çalışmanın amacı konjenital ptozisli 9 olgunun 10 gözüne uygulanan anterior yaklaşımla levator aponevroz cerrahisinin sonuçlarının değerlendirilmesidir. Çalışmaya Şubat 1998-Eylül 2000 tarihleri arasında Elazığ Devlet Hastanesi'ne müracaat eden hastalar alınmıştır. Hastaların 6'sı erkek 3'ü kadın olup ortalama yaşları 15.0 (8-25 yaş), ortalama takip süreleri 11 ay (3-31 ay) idi. Levator cerrahisi sonuçları değerlendirilirken 1mm ve daha altında rezidüel ptozis kalan olgular "başarılı" , 1 - 2 mm rezidüel ptozis kalan olgular "tatminkar", bunun altındaki sonuçlar "başarısız" olarak kabul edildi. Anterior yaklaşım ile levator rezeksiyonu uygulanan gözlerden 7'sinde (%70) başarılı, 2'sinde (%20) tatminkar, 1'inde (%10) başarısız sonuçlar elde edildi. Sonuç olarak anterior aponevroz cerrahisi; Müller kası, Whitnal ligamanı, konjonktiva, levator boynuzları vb. gibi anatomik yapıların korunması ve daha detaylı görülmesi, yeterli kozmetik ve fonksiyonel düzelme sağlaması nedeniyle ptozis cerrahisinde tercih edilmesi gereken bir yöntem olarak düşünüldü.
KONJENİTAL PTOZİSTE ANTERİOR APONEVROTİK YAKLAŞIM